The development of gross motor analysis system software: a preliminary concept - Abdullah, Borhannudin; Wan Jaafar, Wan Marzuki; Mohd Ayub, Ahmad Fauzi (Elsevier, 2012)
The purpose of this paper is to discuss about the design and development of gross motor analysis system software. The concept of the development of gross motor analysis system software was based on observation of researcher about the difficulties faced by sports science educators to analyze the performance of young athletes. This software was developed to help sports science educators to manage the gross motor analysis more systematic and efficient. This software is stand-alone software to enable the sports science educators to install it to their personal computer or office's computer. Only authorized personnel can access to the system using username and password. This is to ensure the gross motor analysis records are well protected. In conclusion, all features in this software were developed to ensure that it help the sports science educators easy to use the system efficiently.